2021
DOI: 10.1002/ange.202101730
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Quenching‐to‐Dequenching Switch in Quantitative Cell Uptake and Biodistribution of Dye‐Labeled Nanoparticles

Abstract: Ag eneral strategy to carry out cell uptake and biodistribution studies is to label nanoparticles (NPs) with afluorescent dye.However,the comparative study of different dye-loaded NPs remains difficult owingt ou ncontrolled dye quenching and de-quenching. Here we compared two types of dye-labeled NPs and demonstrated their distinct properties. NPs with dye molecules at as olid state suffer from dye quenching, so the dye release and/or NP degradation in biological environments leads to as everal-fold increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The fluorescence intensity of Cy3 or Cy5 leveled off with increasing particle concentration (Supplementary Figure S1) likely due to selfquenching. As reported in previous studies [25,30], this self-quenching phenomenon is dye-concentration-dependent. To avoid this self-quenching, NPs prepared with a fixed amount of 1 wt% Pep-Cy3 in the feed were selected for the preparation of FRET NPs containing 1.5-9 wt% PLGA-Cy5, corresponding to molar feed ratios of donor dye (Cy3) /acceptor dye (Cy5) (D/A) ranging from 5:1 to 0.8:1.…”
Section: Characteristics Of Single-and Dual-labeled Plga Nanoparticlessupporting
confidence: 81%
See 2 more Smart Citations
“…The fluorescence intensity of Cy3 or Cy5 leveled off with increasing particle concentration (Supplementary Figure S1) likely due to selfquenching. As reported in previous studies [25,30], this self-quenching phenomenon is dye-concentration-dependent. To avoid this self-quenching, NPs prepared with a fixed amount of 1 wt% Pep-Cy3 in the feed were selected for the preparation of FRET NPs containing 1.5-9 wt% PLGA-Cy5, corresponding to molar feed ratios of donor dye (Cy3) /acceptor dye (Cy5) (D/A) ranging from 5:1 to 0.8:1.…”
Section: Characteristics Of Single-and Dual-labeled Plga Nanoparticlessupporting
confidence: 81%
“…This indicates that Pep-Cy3 in the present study, in line with the previous findings, was partly released from the PLGA NPs. Recently, Yang et al [30] reported dequenching of Dil fluorescence mediated by the release of the Dil dye loaded in Cy5-labeled PLGA NP. In line with the study of Yang et al [30], the observed increase in Cy3 fluorescence of both Pep-Cy3 NP and FRET NP probably points to the dequenching of Cy3 fluorescence due to the release of Pep-Cy3 from the PLGA NP.…”
Section: Colloidal Stability and Time-dependent Fluorescence Of Label...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absolute intensity of a single fluorescence dye is often inaccurate and non-comparable because many factors could affect its intensity, including background signal, instrumental set-up, and materials screening and quenching. Furthermore, the fate of NPs in vitro or in vivo cannot be accurately monitored by using fluorescence-dye-labelled NPs, as the dye might be already separated from the NP itself due to release or degradation [3,4]. Therefore, single fluorescence probes cannot be used for the accurate monitoring of NP drug delivery.…”
Section: Introductionmentioning
confidence: 99%